205k views
3 votes
Prove that (AB)−1=B−1A−1

1 Answer

1 vote

Answer with Step-by-step explanation:

Consider,


(AB)^(-1)(AB)=I (Identity rule)

Multiplying by B⁻¹ on the both the sides, we get that


(AB)^(-1)(AB)B^(-1)=IB^(-1)\\\\(AB)^(-1)A(BB^(-1))=B^(-1)

And we know that BB⁻¹ = I

So, it becomes,


(AB)^(-1)A=B^(-1)

Now, multiplying by A⁻¹ on both the sides, we get that


(AB)^(-1)AA^(-1)=B^(-1)A^(-1)\\\\(AB)^(-1)=B^(-1)A^(-1) (AA⁻¹=I)

Hence, proved.

User Julio Di Egidio
by
4.6k points